Impact of climatic shocks on child human capital: evidence from young lives data. (2nd July 2016) - Zamand, Mina; Hyder, Asma
ABSTRACT: This study attempts to assess the impact of two different climatic shocks, drought and excessive rainfall/flood, as perceived by households on child human capital across four countries: Ethiopia, India, Peru and Vietnam – countries with diverse socio-economic backgrounds. Human capital, in this context, subsumes both child learning and health outcomes. The data source is the Young Lives Study and cross-sectional household data on the older cohort of children (between 14 and 16 years of age) are utilized, for the year 2009. The enrolment rate, Peabody Picture Vocabulary Test, Cloze test and Math test scores are used as proxies for child learning outcomes. The health outcome variables being studied are the WHO-defined Body Mass Index z -scores and Height for Age z -scores. The overall objective is to study heterogeneity in responses to shock in terms of the development of human capital across the set of countries considered. Additionally, the study elaborates on the role of institutional help, during crisis, and the role of household characteristics in buffering these climatic shocks.